التصميم الانشائي لمكتبة عامة " - الحلايقة, أسيل; التلبشي, ريناد; برادعية, ناردين (جامعة بوليتكنك فلسطين - كلية الهندسة - مباني, 2016)
Project Abstract The library is open places to get the information in its various forms and multiple sources in order to search and view. The metaphor is the cornerstone to the success of the services and activities provided for readers and visitors to these libraries . The study of design libraries buildings is important studies, so as it represents the buildings of an important element to attract readers on them, as these libraries success in achieving cultural and social goals and the other depends on the fulfillment of its buildings to the standards optimum space, appropriate to the site, and the necessary equipment, which take into account the specificities and needs of each class of audiences, and we have interest in and emphasis on the need to exit the difficult equation that combines the least cost and maximum benefit and designed to adapt to the surrounding environment and social conditions. In this project we make a structural design of the " general library", where consists of three floors , where a total area of 3000 m^2, the project will include the construction elements known from the nodes, and bridges, columns, and foundations… etc. The project will include a detailed structural study of the identification and analysis of the elements of construction and different loads expected and live loads by used Jordan's code and the USA Code (ACI_318), then the preparation of shop drawings based on the prepared for all the structural elements that are structural frames of the building, it must be noted that it will rely on some computer programs such as: AutoCAD 2007,Office2010, ETABS, BEAMD,SAFE 12,Staadpro,Atir .
مكتبة التحرير
cd, 16160 ,no of pages 80 , مباني 14/2016 ,in the store
Keywords: مكتبة التحرير